Tunable dynamic properties of hydrogen-bonded supramolecular assemblies in solution. (January 2021) - Vereroudakis, Emmanouil; Vlassopoulos, Dimitris
Abstract: Supramolecular polymers have emerged as a scientifically challenging and technologically important field of polymer science, because of the dynamic nature of the secondary bonds which govern their self-organization and their macroscopic properties. Their response to environmental parameters (temperature, solvent, pH, humidity) offer unprecedented tunability, enabling applications in diverse fields ranging from biomaterials to microelectronics. Thanks to the advances in supramolecular and organic chemistry, the field has gained tremendously in relevance and the fine-tuning of molecular structure has yielded a rich diversity of self-assemblies in solution and in the melt, whose consequences on the respective rheological and mechanical properties are significant but not fully understood. It is clear that the plethora of (mostly) experimental evidence needs to be grouped thematically in order to define the basic knowledge and outstanding issues and eventually advance the field. In this brief review we attempt to contribute in this direction by focusing on solutions of living polymers based on hydrogen-bonding moieties. In this review, we summarize the different possibilities to obtain such supramolecular assemblies, their structural and linear viscoelastic properties along with the basic framework for understanding them, as well as their response to different external fields. We outline the major open challenges, especially regarding nonlinear rheology and briefly discuss the perspectives of this exciting field. Graphical abstract: Image, graphical abstract